Training the novice teacher in the Pedagogy Department of Education of the University of the Andes, Tachira - Mireya Vivas de Chacón; Gladys Becerra Torres; Dámaris Díaz Herrera (Universidad Autónoma de Baja California, 2005)
This article presents the results of a case study whose objective was to describe the process of training first-year college teachers. The information was collected through in-depth interviews. In the context investigated, the novice teachers do not get enough institutional support in their new jobs and develop their work alone, since they do not carry on research or learn to teach alongside more-experienced teachers. The new teachers said they felt nervous, insecure, rejected, distressed, alone and disoriented. The results of this study reveal a disparity between what is demanded by the rules established for the training of new university teachers, and what actually happens in the departments. This is because training plans are not carried out, and training is considered to be the responsibility of the novice teacher. Finally, recommendations are made for the development of a training policy for new faculty members.